Physical-mechanical, chemical and biological properties of graphene-reinforced glass ionomer cements - Tatiane Ramos dos Santos Jordão; Laura Soares Viana Fernandes; Karla Lorene de França Leite; Adílis Alexandria; Emmanuel João Nogueira Leal Silva; Lucianne Cople Maia; Tatiana Kelly da Silva Fidalgo (Restorative Dentistry & Endodontics)
ObjectivesThis study aimed to evaluate the physical-mechanical, chemical, and biological properties of graphene-reinforced glass ionomer cements (GICs).Materials and MethodsDifferent proportions of graphene powder were incorporated into 2 high-viscosity self-curing GIC, Ketac Molar (GKetac) and Fuji IX (GFuji), in 4 different concentrations: 0.5%, 1%, 2%, and 5%. The control groups included the GICs without graphene. Experiments were performed to analyze linear (Ra) and volumetric roughness (Sa), antimicrobial activity, radiopacity, fluoride release, microhardness, solubility, and water sorption. Data were analyzed using Kruskal-Wallis, Mann-Whitney, Wilcoxon, analysis of variance, and Tukey’s test (p ≤ 0.05).ResultsThe GKetac 0% and GFuji0% groups presented higher Ra (4.05 and 2.72) and Sa (4.76 and 5.16), respectively. No inhibition zone was observed, and the incorporation of graphene reduced radiopacity. Moreover, there was no influence on the solubility and water sorption after 21 days. A greater fluoride release was observed in the period of 7 days for most of the groups. After 21 days, GKetac 5%, 2%, and 1% presented higher releasing than 0% and 0.5% (p ≤ 0.05).ConclusionsThe graphene incorporation improved the microhardness of GICs in lower concentrations. Graphene incorporation to GICs modified some physical-mechanical, and chemical, but not affected biological properties.